(untitled) (Social Inquiry: Journal of Social Science Research, 2023)
Enrollment of the students or the participants in any institution or training can directly determine the prosperity of the schools and the institutions. Institutions are working hard primarily for their survival and gradually for their stability and long-run businesses for the future. The education and training existing in urban areas and it is in rural areas differ in many respects. Technical Education in urban areas and it is in rural as well as remote rural has diversified thoughts in terms of enrollment issues of the students. It is urgent to know the interests of the students and participants, as well as why and how they are attracted to go for technical education or the general stream in the community. It is realized that there are relatively not only fewer students but also a smaller proportion of students in the enrollment. It seems like there are various areas that the current government should focus on for the sake of technical and vocational education and training (TVET) development regarding the enrollment issues in the Technical Education in Community Schools (TECS) modality program. The number of TECS modalities accredited is increasing trend in the country, but it is not realized as it should be by enrolling a higher number of students each year in multiple folds. Or the students are becoming self-driven, having their core interest to enroll for the course. The issues are very closely studied by going through the secondary data in education, papers, magazines, journal articles, books and many similar other resources through the internet and the informal pool.